State-of-the art iris segmentation methods: A Survey - Satish, R; Kumar, P. Rajesh (International Journal of Computer Sciences and Engineering, 2025)
In today’s world scenario where security and privacy are the primary concern, the systems that are developed must employ accurate techniques to achieve this. The biometric recognition provides automated verification of individuals based on unique characteristics processed by an individual. The commercial biometric systems are popular and are used extensively, but not restricted to, in the fields of banking services, access secured database, airport surveillance, access control in the boarders etc. Biometric systems are developed based on the physical or behavioural unique characteristics of the individuals. Iris recognition system is the most reliable and accurate, which is grabbing the attention of the researchers now a day. The iris epigenetic patterns are unique, stable and accurate when compared with the other biometric traits. The iris recognition system is a very good research topic in the areas digital image processing, computer vision & pattern recognition. The segmentation or localization is a very crucial stage, because the system’s accuracy highly relies on segmentation. In this paper, detailed state-ofthe-art segmentation techniques have been presented